2020
DOI: 10.1016/j.jtho.2020.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib Improves Overall Survival in Patients With EGFR-Mutated NSCLC With Leptomeningeal Metastases Regardless of T790M Mutational Status

Abstract: Introduction: Osimertinib, a third-generation EGFR tyrosine kinase inhibitor, efficiently penetrates the blood-brain barrier. This study explored whether treatment with osimertinib leads to improved overall survival (OS) for patients with EGFR-mutated NSCLC with leptomeningeal metastases (LM) compared with those not treated with osimertinib. Methods: From October 2008 to October 2019, patients with EGFR-mutated NSCLC and cytologically confirmed LM were retrospectively analyzed for OS according to osimertinib t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 22 publications
(27 reference statements)
3
54
1
Order By: Relevance
“…High-dose erlotinib (200 or 300 mg every 2 days, or 300 or 450 mg every 3 days, or 600 mg every 4 days) and pulsatile high-dose erlotinib (median dose 1500 mg, weekly) achieved radiographic responses of 30% and 67%, respectively, compared with standard doses of erlotinib or gefitinib in patients with EGFR mutant NSCLC with rLM (9,22). Osimertinib is a third generation EGFR-TKI that effectively penetrates the blood-brain barrier (23), and a previous study had reported that osimertinib improves OS in NSCLC patients with rLM regardless of T790M mutation status (24). The BLOOM study demonstrated a meaningful treatment effect of highdose osimertinib (160 mg daily) in patients with EGFRmutant NSCLC with rLM (positive CSF cytology) and a manageable safety profile (11).…”
Section: Discussionmentioning
confidence: 99%
“…High-dose erlotinib (200 or 300 mg every 2 days, or 300 or 450 mg every 3 days, or 600 mg every 4 days) and pulsatile high-dose erlotinib (median dose 1500 mg, weekly) achieved radiographic responses of 30% and 67%, respectively, compared with standard doses of erlotinib or gefitinib in patients with EGFR mutant NSCLC with rLM (9,22). Osimertinib is a third generation EGFR-TKI that effectively penetrates the blood-brain barrier (23), and a previous study had reported that osimertinib improves OS in NSCLC patients with rLM regardless of T790M mutation status (24). The BLOOM study demonstrated a meaningful treatment effect of highdose osimertinib (160 mg daily) in patients with EGFRmutant NSCLC with rLM (positive CSF cytology) and a manageable safety profile (11).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with EGFR mutation-positive advanced NSCLC, there is an unmet need for EGFR-TKIs with improved central nervous system (CNS) penetration and activity against CNS metastases, either at initial diagnosis or time of progression [ 30 ]. OSI was shown to have a good brain exposure in human subjects [ 31 ] and to be active against CNS brain metastases or leptomeningeal disease, regardless of T790M status [ 30 , 32 , 33 ]. Patients with brain metastasis may benefit from treatment with liposome-based OSI delivery due to favorable blood-to-brain penetration of the drug and additionally by brain targeting route of administration.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, Lee et al 22 reveal that osimertinib significantly prolongs OS in patients with EGFRm NSCLC and LMD irrespective of the sequence of the therapy. This is a significant improvement in survival for patients with LMD who have thus far been excluded from clinical trials, lack standardized response assessment methods, and treatment guidelines.…”
mentioning
confidence: 83%
“…Throughout this study period (October 2008-October 2019), the treatment paradigm for metastatic EGFRm NSCLC has evolved, with osimertinib becoming the standard-of-care first-line (1L) therapy irrespective of EGFR T790M mutation status. Lee et al 22 found no OS advantage with a higher dose of osimertinib. This study further reinforces the excellent CNS bioavailability of osimertinib, and CNS failure seems to be less common with osimertinib.…”
mentioning
confidence: 97%
See 1 more Smart Citation